Pengaruh Harga, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Cehay Pada Toko Hayati Di Kabupaten Tangerang - Alfi Yunia Nanda; Agung Wijoyo (Shofanah Media Berkah, 2026)
This study aims to analyze the effect of price, product quality, and promotion on purchasing decisions of Cehay products at Hayati Store in Tangerang Regency. The research problem arises from fluctuating sales performance and purchasing decisions that are not yet optimal, which are assumed to be influenced by consumers’ perceptions of price, product quality, and promotional activities. This research employed a quantitative approach with a sample of 69 respondents determined using Slovin’s formula. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results indicate that price, product quality, and promotion partially have a significant effect on purchasing decisions. Simultaneously, the three variables also significantly influence purchasing decisions with the regression equation Y = 12.403 + 0.295X₁ + 0.106X₂ + 0.363X₃. The coefficient of determination of 31.0% shows that purchasing decisions are influenced by price, product quality, and promotion, while the remaining percentage is affected by other factors outside this study. These findings emphasize the importance of integrated marketing strategies to improve consumer purchasing decisions.